Comparing Manuka and other medical honeys as adjunct to antibiotic therapy against facultative anaerobes - Sievers, Justus Thomas Obiajulu; Moffat, Emily; Khadijah Yusuf; Sarwar, Nabaa; Bowolaksono, Anom; Fyfe, Lorna (Penerbit Universiti Kebangsaan Malaysia, 2022)
The development of antibiotic resistance in pathogenic bacteria has created a push for new treatments, with honeys (especially Manuka) becoming a common focus due to their strong antimicrobial action. However, alternatives to Manuka are necessary, as its production is vulnerable. Additionally, research is lacking on how honey affect facultative anaerobic bacteria grown in anaerobic conditions and how honey and antibiotics interact in these conditions. In order to understand these interactions and find novel honey candidates, we investigated the antibacterial effects of four honeys (two Manuka, one Chilean and one ‘Santa Cruz’ honeydew honey) against Staphylococcus aureus and Pseudomonas aeruginosa grown aerobically and anaerobically in broth cultures, and how the honeys affected the action of common antibiotics against these bacteria using agar diffusion assays. We found all honeys to be highly effective at 75% honey, with no significant differences between honeys, showing that other honeys were suitable alternatives to Manuka at such high concentrations. At 20%, oxygen availability and bacterial species impacted the effectiveness of honeys as Santa Cruz honey was most effective aerobically but failed anaerobically, while Manuka honeys were effective against S. aureus but not P. aeruginosa in both conditions, and Chilean honey was ineffective against all samples. The addition of honey increased bacterial sensitivity to antibiotics in some cases, varying with aerobic conditions. The antibacterial activity of the honeys, and differences in conditions whether aerobically or anaerobically, were not correlated with pH, antioxidant capacity or total phenolic count. Since in all cases honeys were either beneficial or of no effect, these results supported the use of honey as adjunct to antibiotic therapy in scenarios such as on bandages, with honeys other than Manuka also being worth consideration.